2018
DOI: 10.4244/eij-d-18-00064
|View full text |Cite
|
Sign up to set email alerts
|

Pressure wire compared to microcatheter sensing for coronary fractional flow reserve: the PERFORM study

Abstract: Introduction of the PC reduced both hyperaemic FFR and resting Pd/Pa compared with the PW alone, leading to re-classifying physiological significance to below the clinical threshold in one out of five assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Six studies, including stenosis-level data from 440 lesions (413 patients), were included in the final analysis (figure 2). 1 3–7 All studies compared FFR MC to FFR PW and provided scatter plots that enabled extraction of raw data. The sample size, means and SD of extracted data points were numerically identical to those reported in each study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies, including stenosis-level data from 440 lesions (413 patients), were included in the final analysis (figure 2). 1 3–7 All studies compared FFR MC to FFR PW and provided scatter plots that enabled extraction of raw data. The sample size, means and SD of extracted data points were numerically identical to those reported in each study.…”
Section: Resultsmentioning
confidence: 99%
“…In all five studies where the method of drift measurement was recorded, drift was measured separately for the PW and MC. Of the four studies that presented a point estimate of signal drift,4–7 only one presented individual patient data 4. In three of these studies,5–7 no clinically significant difference in the mean level of drift between FFR MC and FFR PW was reported table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a hypothesis exists that the fiber‐optic based pressure sensor has less drift compared with piezoresistive sensors 12 . However, until now, this hypothesis has not been well verified: while Menon et al found optical‐sensor PMC has smaller mean drift than piezoresistive PW ( p = .014), 28 Wijntjens et al, 13 Fearon et al, 14 and Ali et al 15 all reported that the mean drift of the two systems do not differ statistically ( p = .07, .66, and .38, respectively). The findings are similar when comparing the mean drift of optical‐sensor PW with piezoresistive PW 21 .…”
Section: Discussionmentioning
confidence: 99%
“…An optical‐sensor pressure microcatheter (Navvus, ACIST Medical Systems, Eden Prairie, MN, USA) accommodating any 0.014″ guidewire has been developed 12 and investigated in several clinical studies. 13 , 14 , 15 , 16 It has been shown that FFR measurement using pressure microcatheter (PMC) facilitates multiple advancement and withdrawal over any guidewire of physicians' choice. In addition, during physiological assessment for diffuse and serial lesions, the PMC enables maintaining the guidewire in place.…”
Section: Introductionmentioning
confidence: 99%